A prominent bathochromic shift effect of indole-containing diarylethene derivatives. Issue 11 (10th February 2015) - Cheng, Hong-Bo; Huang, Yao-Dong; Zhao, Lina; Li, Xu; Wu, Hai-Chen
Abstract : Bisindole diarylethene derivatives exhibit a strong bathochromic shift effect in photochromism compared with bisbenzothiophene diarylethene. Abstract : The potential implication of photochromic materials with absorption and reactivity in the near-infrared region is far-reaching. In this work, three novel bisindole-containing diarylethene derivatives1o–3o have been successfully synthesized and their photochromic behaviour exhibits a strong bathochromic shift effect compared with bisbenzothiophene diarylethene4o . These new bisindole-diarylethene compounds1o–3o are highly sensitive to photo-stimuli both in solution and in poly(methyl methacrylate) films. Besides, 1o–3o exhibit an excellent reversible fluorescence switching behavior modulated by optical stimuli.